2002
DOI: 10.1176/appi.ajp.159.6.991
|View full text |Cite
|
Sign up to set email alerts
|

The General Fertility Rate in Women With Psychotic Disorders

Abstract: This study found markedly lower fertility rates in women with psychotic disorders than in matched normal comparison subjects, particularly in women with non-affective disorders. Knowledge of fertility rates in women with psychotic disorders is fundamental for clinicians and researchers, since it has implications for family planning services, prevention of obstetric complications, child-care support, and hypotheses about the etiology of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 22 publications
8
38
2
2
Order By: Relevance
“…Psychiatric illness may affect opportunities for marriage and motherhood and decisions about subsequent childbearing. [17][18][19][20] Women who are depressed are less likely to have stable relationships, probably because of the impact of the illness on their behaviour. 21 Research has shown that men become depressed when their wives are depressed.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric illness may affect opportunities for marriage and motherhood and decisions about subsequent childbearing. [17][18][19][20] Women who are depressed are less likely to have stable relationships, probably because of the impact of the illness on their behaviour. 21 Research has shown that men become depressed when their wives are depressed.…”
Section: Discussionmentioning
confidence: 99%
“…People with bipolar disorder seem to be more successful at making relationships (although they may have difficulty maintaining them over long periods of time), than those with schizophrenia. They have higher marital rates and higher fertility rates, although studies show that their fertility rates are lower than those in the general population (Lane 1995;Howard 2002). Vogel (1979) found that earlier onset of illness (psychic disturbance before the age of 15) is associated with a worse reproductive outcome and suggested that this is related to the greater personality disturbance seen in those with early-onset disease.…”
Section: Psychological and Social Factors Implicated In Sexual Dysfunmentioning
confidence: 99%
“…The number of babies born to mothers with psychosis aged 25 and older (accompanied by no affective symptoms) is lower than in the general population average for females [27]. However, there is no difference between women suffering from schizophrenia and healthy women in successfully reproducing over all ages.…”
Section: Motherhood and Schizophreniamentioning
confidence: 89%
“…However, there is no difference between women suffering from schizophrenia and healthy women in successfully reproducing over all ages. The lower rates may also be influenced by other variables not readily considered such as lower rates of sexual activity, difficulties maintaining stable romantic relationships [27], medication induced abnormalities in prolactin levels and menstruation (which can vary depending on which medication is taken) [28] and medication induced sexual dysfunction (30-80% in women) [29][30][31]. It has been shown that more than half of the women with psychosis in the sample for the McGarth group (1999) were mothers and had higher levels of fertility was associated with a later age at first diagnosis [32].…”
Section: Motherhood and Schizophreniamentioning
confidence: 99%